Experimental and numerical investigation of seismic response of access floors based on shake-table tests using 2-story steel moment frame - Jun, Su Chan; Jung, Dam I.; Lee, Cheol Ho; Cho, Bong Ho (Journal of Building Engineering, 2023)
In this study, a full-scale shake-table test was conducted utilizing a 2-story steel moment frame to evaluate the seismic performance of access floors (or raised floors). A total of four access floor specimens were fabricated that are typically used in offices and computer/server rooms. Based on test results, critical failure modes and nonlinear behavior of access floors were discussed in detail. Specimen utilizing a flexible 600 mm-high access floor (FH600-F) exhibited several cracks in its joint connection plates (or pedestal heads) before the specimen eventually collapsed under the 60% RRS intensity test (PFA = 0.65 g). Due to a partial pull-out of the pedestal heads from their supporting columns, a highly pinched hysteretic response was also observed. A simplified SDOF numerical model was presented that can effectively capture the complex pinching behavior of access floor specimens. Based on the calibrated numerical analysis, it was identified that the partial pull-out of pedestal heads caused about 60% strength loss during the reverse cyclic phase of the specimen, which was the main source of the high pinching. The specimen also exhibited severe stiffness-degradation, which may have resulted from the cracks that developed in a significant number of its joints. The initial stiffness of the specimen was reduced by about 30% before its eventual collapse. Extensive numerical analyses were also conducted to evaluate the effects of pinching and stiffness-degradation on the acceleration response of access floors based on the floor motions obtained from the time history analysis of four multi-story building models.
Keywords: Access floor; Experimental investigations; Non-structural elements; Numerical investigations; Pinching behavior; Pull-out; Seismic Performance; Shake-table tests; Steel moment frames; Stiffness degradation; Access floor; Nonstructural element; Numerical model; Pinching behavior; Shake table test